Analysis of International Migration and its Impacts on Developing Countries - Paola Barrientos (Institute for Advanced Development Studies (INESAD), 2007)
This paper provides a review of the literature on the reasons and consequences of international migration. The principal determinants of migration are analyzed and it is seen that educated people from developing countries are more likely to migrate for several reasons (i.e. network determinants, costs of moving, pull factors and push factors). Looking into the empirical data, the global trend is that emigration of educated people (usually called brain drain ) has increased a lot. This trend implies that industrialized countries are importing highly skilled people from developing countries and this will certainly have important consequences for developing countries in the long run. Some researchers argue that developing countries will loose, since the most qualified people leave and stop contributing to their country. Others say that the global trend can be beneficial because positive spillovers will be created; in the sense that developing countries will experience higher investments in human capital ( brain gain ). Empirical findings show that these spillovers depend on the probability to migrate and the stock of human capital that a country has. Finally another group of researchers argues that this process is inevitable, and barriers to migration should be abolished in order to reap the benefits for both sending and receiving countries as well as the migrants themselves.
Keywords: F22; O15; 330; Migration; Brain Drain; Brain Gain